Microskills Training: A Model for Teaching Verbal Processing Skills in Music Therapy - Gooding, Lori Fogus (Voices: A World Forum for Music Therapy, 2017)
Music therapy scholars have suggested that verbal processing is widely integrated into music therapy practice, though specific implementation varies based on the therapeutic approach and the clients’ level of functioning. Results from music therapy studies have suggested that clients find verbal processing both important and useful, yet the development of verbal processing skills can be difficult for music therapists and music therapy students. Given the complexity of the skills needed, inclusion of a model or framework may help focus and organize skill development. One model that may have wide utility among music therapy practice is the microskills model (microcounseling). Microcounseling is built upon ethical and cultural competence, addresses skills in a hierarchical manner, and can be combined with a number of theoretical approaches. Research shows that this model has been successfully translated into 21 languages, used in a range of helping professions, and taught in both traditional and self-instruction formats. Perhaps most importantly, the model initially focuses on skills needed by all music therapists, regardless of theoretical orientation, and then progresses to skills needed to effectively facilitate common music therapy interventions like song discussion. Combining this model with other elements of music therapy education may better promote skill development and guide music therapists in skill usage.